Book Review - Kilchör, Benjamin (Old Testament Essays, 2020)
Georg Fischer, Genesis 1–11, Herders Theologischer Kommentar zum Alten Testament, Freiburg i. Br.: Herder, 2018, 752 pages, hardcover, € 115.00, ISBN 978-3-451-26801-4. https://doi.org/10.17159/2312-3621/2020/v33n1a11